Electromagnetic design of a 220 GHz BWO with experimental study of micro-fabricated folded waveguide structure. Issue 14 (22nd September 2019) - Srivastava, Anurag; Penmetsa, Siva; Christie, Latha; Bhat, K. N.
ABSTRACT: Backward-wave oscillator (BWO) is the most promising source for the generation of a few watts of power at millimetre wave and sub-millimetre wave frequencies. This paper presents the electrical design of a folded waveguide BWO at 220 GHz. The dispersion of the structure was theoretically calculated and further validated by numerical simulation using CST MWS. A minimum output power of 5 W at 220 GHz, was obtained using the particle-in-cell simulation of CST MWS, at the beam voltage of 10 kV and a current of 50 mA. Also, a power of around 1 W is obtained over a band of 4.5 GHz by voltage tuning. The ultra-thick ∼750 µm height Au-structure is fabricated using multi-step photolithography and etching processes while keeping the surface roughness well below the skin depth. The slow wave structure was tested and it was found that the return-loss is in good agreement with the simulation results within ∼5 dB, throughout the 185–260 GHz band.